14m-5(m-2)+26=0

Simple and best practice solution for 14m-5(m-2)+26=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14m-5(m-2)+26=0 equation:


Simplifying
14m + -5(m + -2) + 26 = 0

Reorder the terms:
14m + -5(-2 + m) + 26 = 0
14m + (-2 * -5 + m * -5) + 26 = 0
14m + (10 + -5m) + 26 = 0

Reorder the terms:
10 + 26 + 14m + -5m = 0

Combine like terms: 10 + 26 = 36
36 + 14m + -5m = 0

Combine like terms: 14m + -5m = 9m
36 + 9m = 0

Solving
36 + 9m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 9m = 0 + -36

Combine like terms: 36 + -36 = 0
0 + 9m = 0 + -36
9m = 0 + -36

Combine like terms: 0 + -36 = -36
9m = -36

Divide each side by '9'.
m = -4

Simplifying
m = -4

See similar equations:

| -31-4x=-10(1+5x) | | 3+4b-14=15-5b-4b | | 4y+3x=1368 | | h(t)=-2t^2+12t-11 | | (17x+8)-5=20 | | 3y+4x=1368 | | 5x/2-4=5 | | 3+4b-14=15-5b-4bford | | -(x+2)+5x=6x+14 | | h(t)=-2t^12f+11 | | g+g+2=1000 | | x+45+6x-5=180 | | 5x^2-6x+7+8x+4+5x^2= | | 4e(2x+1)=20 | | -2x/-1 | | 3a+5b=63 | | 5/11t=7(5-2t) | | sin(x)=0.857633 | | -x^2/-1 | | 0.72x=7.5 | | N-17=4(1-5n) | | 3(x-7)/2=15 | | (3.4x)+7=x+54.6 | | 2x+4x-9+x^2+2x+9=180 | | 0=x^2+13x+30 | | 13n=.26 | | 3x-1=0.50(4x+6) | | 6x^2+36+48=0 | | -7x-8=4x+6 | | 4/13p=-16/5 | | -8/3÷3 | | -18=0(-3)+b |

Equations solver categories